WOMEN EMPOWERMENT AND COMMUNITY DEVELOPMENT IN OKIGWE LOCAL GOVERNMENT AREA OF IMO STATE, NIGERIA - Ubah, Chukwudi Nelson (African Journal of Social and Behavioural Sciences, 2025)
The study examined women's empowerment and community development in Okigwe LGA, Imo State. Three research objectives, three research questions and three research hypotheses guided the study. Descriptive survey research design was used, and a questionnaire served as the instrument of data collection. A total of 176 participants were selected as the study sample. The data collected were presented in tables and analysed using simple percentages, and the hypotheses were tested using chi-square. Based on the data analysis, the findings revealed that there is a significant impact of educational empowerment on women's contribution to community development; there is a significant relationship between skill acquisition for women and community development; and employment of women contributes to women's community development. The significance of the above findings is that it will add positive values to self-reliance among women when they are properly empowered. Based on the findings, it was recommended that the Nigerian government should empower women through educational and technical training to enable them to contribute significantly in community development. More so, women in good positions should try significantly to prove that they have significant things to offer in promoting community development, peace and harmony and unity in society.